Two new species of Clypeocaenis (Ephemeroptera: Caenidae) from Western Ghats, Southern India - Muthukatturaja, Marimuthu; Balasubramanian, Chelliah; Murugan, Alagumalai (Zootaxa, 2020)
Two new species of Clypeocaenis (Ephemeroptera: Caenidae) are described from Gayathripuzha River, Kerala, and Tunga River, Karnataka, Southern India. The species are best distinguished from congeners based on leg and gill characteristics, as follows. Clypeocaenis gayathri sp. nov.: (1) fore tibia with two rows of ventral and lateral filtering setae, femur with bifid spines, middle tibia with trifurcated spines apically; (2) tracheated gill covers with spines and bifurcated ridges on margins, gills III–VI with more numerous fringed bifid fimbriae. Clypeocaenis sharadhae sp. nov.: (1) fore tibia with two rows of long filtering setae on lateral margin and one row on ventral margin arranged vertically, fore tarsus with transverse row of long setae, hind tibia with a row of lanceolate setae on lateral margin; (2) gills III–VI approximately triangular shaped, with fringed bifid fimbriae, gill III with 12 bifurcated and 2 trifurcated fimbriae.